GENDER INEQUALITY REFLECTED IN SHORT STORY SWEAT BY ZORA NEALE HURSTON - Pasuhuk, Natasya; Maru, Mister Gidion; Andries, Fivy A. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
This study aims to find out the evidence of gender inequality experienced by Delia Jones in Zora Neale Hurston’s Sweat. The writer used a qualitative method in conducting this research. In collecting data, the writer uses two sources: the first is primary source, namely the literary work Sweat by Zora Neale Hurston, while secondary sources are references such as journals, books, and internet sources related and relevant to the research. In data analysis, the writer uses a feminist approach to analyze gender inequality. The result shows that Delia’s life as the main female character experiences several types of gender inequality that she must face in her life, such as marginalization, subordination, and violence. She can finally feel happy because she can be free from the threats that bind her. Her patience and wisdom brought her to safety. The writer hopes that through this research, readers can learn not to think that gender inequality is common because, basically, women have the same rights as men and should use wisdom to fight for life when our strength is limited.